2008
DOI: 10.1017/s0010417508000133
|View full text |Cite
|
Sign up to set email alerts
|

Skulls and Scientific Collecting in the Victorian Military: Keeping the Enemy Dead in British Frontier Warfare

Abstract: As a result of colonial wars with indigenous peoples, especially in Africa and North America, a distinction seems to have arisen in Western military culture between ‘civilized’ and ‘savage’ enemies. The behavior of civilized enemies in battle appeared rational and constrained by rules. Savage enemies, on the other hand, evinced emotional and unregulated violence. Above all, they were distinguished by an excessive brutality they seemed to display towards their enemies in customs such as cannibalism and the taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 11 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…However, I have suggested that these actions were, in part, local symptoms of shifts taking place after the Enlightenment in the ways in which human diversity was conceptualized. These changes were felt and expressed in scientific or academic circles and, sometimes in unexpected forms, elsewhere in American and European societyincluding, it appears, in the practices of soldiers on the battlefield (Harrison, 2006(Harrison, , 2008.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, I have suggested that these actions were, in part, local symptoms of shifts taking place after the Enlightenment in the ways in which human diversity was conceptualized. These changes were felt and expressed in scientific or academic circles and, sometimes in unexpected forms, elsewhere in American and European societyincluding, it appears, in the practices of soldiers on the battlefield (Harrison, 2006(Harrison, , 2008.…”
Section: Resultsmentioning
confidence: 99%
“…In the 1820s and 1830s, a particular variety of body-snatching or grave robbery developed, whose purpose was not necessarily to obtain the entire body, but specifically the head or skull. Military personnel were among the first sections of European and American society to become involved in this enterprise (Harrison, 2008). From the 1820s, the collection of 'Indian crania', for example, became what Bieder (2003: 67) has called a 'cottage industry' among soldiers and military physicians serving on the American frontier (see also Thomas, 2000).…”
Section: In the Original)mentioning
confidence: 99%
“…85 As Simon Harrison has described, 'Kitchener's treatment of the Mahdi's remains was a post-mortem settling of scores over the death of Gordon, and the mutilation of his body.' 86 Gregson's album may be viewed as an extension of this rationale and as such, these photographs are not innocent and can be viewed as part of the atrocity. 87 Clearly, the relationship between the photographer and the photographed within a colonial context also represented colonial power over the colonised -colonial power relations were, as I discussed above, articulated throughout photographs from this period.…”
Section: 'Khartum 1898'mentioning
confidence: 99%
“…As a bounty had been placed on Mkwawa, his head was cut-off and given to the Regional Governor of Iringa, Tom Prince (Musso 2011). The head was boiled to remove the flesh and the skull was displayed as a trophy at the Prince residence (Baer & Schröter 2001;Harrison 2008). Not only would Prince be rewarded for his service with the heredity title "von" and other honours by the German authorities but was also required to move to a new post and region (Harrison 2008: 295).…”
Section: Chief Mkwawa and The Uprisingmentioning
confidence: 99%